Flight - Zemeckis, Robert, 1952-; Gatins, John; Parkes, Walter F.; Burgess, Don, 1956-; Silvestri, Alan; O'Driscoll, Jeremiah; Washington, Denzel, 1954-; Cheadle, Don; Reilly, Kelly; Goodman, John, 1952-; Greenwood, Bruce, 1956-; Geraghty, Brian; et al. (Hollywood, California Paramount Pictures, 2013)
A seasoned airline pilot miraculously crash lands his plane after a mid-air catastrophe, saving nearly every soul on board. After the crash, Whip is hailed as a hero, but as more is learned, more questions than answers arise as to who or what was really at fault and what really happened on the plane.
Originally released as a motion picture in 2012.
Director of photography, Don Burgess ; editor, Jeremiah O'Driscoll ; music, Alan Silvestri ; costume designer, Louise Frogley ; production designer, Nelson Coates ; executive producer, Cherylanne Martin ; associate producer, Heather Kelton.
Denzel Washington, Don Cheadle, Kelly Reilly, John Goodman, Bruce Greenwood, Brian Geraghty, Tamara Tunie, Melissa Leo, Nadine Velazquez, Carter Cabassa, Adam C. (Ciesielski) Edwards, Conor O'Neill, Charlie E. Schmidt, Will Sherrod, Boni Yanagisawa, Adam Tomei, Dane Davenport, John Crow, E. Roger Mitchell, Ravi Kapoor.
MPAA rating: R; for drug and alcohol abuse, language, sexuality/nudity and an intense action sequence.
DVD; Region 1, NTSC; widescreen (2.35:1) presentation enhanced for 16:9 TVs; Dolby Digital 5.1.
English, French or Spanish dialogue with optional Spanish, Portuguese, French or English subtitles, with English audio description.
Keywords: Air pilots -- Drama; Aircraft accidents -- Investigation -- Drama; Alcoholism -- Drama; Drug abuse -- Drama; Video- -- DVD; Airplane crash -- Drama; DVDs; Entertainment DVD; Video recordings for the hearing impaired; Films for the hearing impaired; Films for people with visual disabilities; Drama; Fiction films; Thrillers (Motion pictures)